Sexuality of people with disability and Human Rights: prejudice, discrimination and social barriers to the experience of desire (Research, Society and Development, 2021)
This paper aims to discuss how the sexuality of people with intellectual disabilities remains a taboo in the social environment, from the speeches that make invisible and discriminate sexual desire of people with disability. It seeks to analyze how affection between these people is perceived as “perverted”, as it escapes the normalization parameter of sexuality and understand how the prejudice surrounding the affective relationships of individuals with disabilities reinforces the discourse of marginalization and historical exclusion of this social group, intensifying the stigmas aimed at those who do not fit the pattern of a "healthy" or "no problems" individual. It is intended, contrary to the discriminatory discourse, to contribute to breaking the stereotypes that surround the sexuality of people with intellectual disabilities, through the construction of the right to subjectivity and the experience of sexual desire, just like any other individual. The methodology used consists of an analysis of the object based on a literature review on the subject in the areas of gender and sexuality, human rights and rights of people with disabilities. We used the case study as a method of procedure to analyze injurious comments by blogger Julia Salgueiro against a baby with Down syndrome on Facebook and the developments in the media. As a result, it was found that, according to common sense, people with disabilities are still seen as “asexual”, without desire, or outsiders and therefore, are the target of direct or indirect bans on their right to sexuality by society. Therefore, it is necessary to advance in the debate, giving voice to these subjects and their experiences.